HUBUNGAN PENGETAHUAN DAN KETERAMPILAN DENGAN KEPATUHAN MEMBACA LABEL GIZI MAKANAN KEMASAN PADA IBU BALITA DI KECAMATAN RUNGKUT, SURABAYA - Hanifa Fatmaningtyas; Dini Ririn Andrias (JURNAL PENELITIAN KESEHATAN, 2016)
Reading the food labels including nutritional labels has been listed on Indonesian Nutrition Guideline2014. The result of the study by National Consumer Protection Institute in 2007 stated 94,3% customers inIndonesia haven’t comply on reading food labels. Consumers, including mothers have an important role indetermining consumption for children underfive. Food packaging for children underfive increases due to theincreasing amount of supermarkets that supply packaged food. Mother’s role to control child’s nutritrion intakewas very important because children underfive is a golden period. Reading the nutritional labels on the packageof food is one way to control nutrient intake of children. This study aims to analyze the relationship betweenknowledge and skill on reading nutritional labels with compliance in reading nutritional labels among mothers ofchildren underfive in Rungkut sub district, Surabaya City. This quantitative research used cross sectional designwith 100 respondents who were drawn from population based on proportional random sampling method. Primarydata were taken using interview with questionnaire and fill self-administered questionnaire. Data analysis wasperformed using chi-square test. Results showed that most respondents classified less knowledge Keywords: nutritional labels, knowledge, skill, compliance